Jackson’s theorem for the Kontorovich-Lebedev-Clifford transform - FANTASSE, Yassine; Akhlidj, Abdellatif (Statistics, Optimization & Information Computing, 2025)
In this paper, by using the Kontorovich-Lebedev-Clifford translation operators studied recently by A. Prasad and U.K. Mandal (The Kontorovich-Lebedev-Clifford transform, Filomat 35:14 (2021), 4811–4824.), we prove Jackson's theorem associated with the Kontorovich-Lebedev-Clifford transform.